Strategi Pimpinan Pondok Pesantren Al-Makmur Tungkar Dalam Mengembangkan Sistem Pendidikan di Era Globalisasi - Rahma, Rifka Haida; Yahya, Muhamad; Niimmasubhani, Niimmasubhani; Adona, Putri (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2024)
Globalization has an impact on the progress of science, increasingly sophisticated information and communication technology. Not only that, globalization also has an influence on educational conditions, including Islamic boarding schools. For this reason, in this discussion the author wants to explain the strategy of the leadership of the Al-Makmur Tungkar Islamic Boarding School in developing the education system in the era of globalization. The method that the author uses in this research is a qualitative method with a descriptive approach. In this research the author used Observation, Interviews and Documentation as data collection instruments. After conducting in-depth research, the author found three strategies implemented by the Al-Makmur Tungkar Islamic Boarding School in developing education in the era of globalization, namely: 1) Curriculum Development, 2) Strengthening Islamic Boarding School Management, 3) Improving Facilities and Infrastructure. Furthermore, the author hopes that through this article new issues will emerge in the development of Islamic education in Indonesia.